Iron's Contribution to Children's Cognitive Development throughout the First 1000 Days of Life : A Literature Review: A Literature Review - Shofie Ayu Nur Firdausiyah (Journal of Diverse Medical Research : Medicosphere, 2026)
Background: Iron is an essential micronutrient that plays a critical role in brain development through processes such as myelination, neurotransmitter synthesis, energy metabolism, and synaptogenesis. Iron deficiency during the first 1000 days of life can disrupt neural network formation and lead to long-term cognitive impairments that are often irreversible. Objective: This literature review aims to analyze the contribution of iron during the first 1000 days of life to children’s cognitive development and to emphasize the importance of nutritional interventions starting from pregnancy. Methods: This literature review was conducted using primary research articles published in English or Indonesian between 2020 and 2025. Relevant studies were identified through systematic searches in PubMed, ScienceDirect, Google Scholar, and ResearchGate, employing the PICO framework and appropriate keywords.Results: Adequate iron status from pregnancy through early childhood is crucial for optimal cognitive development. Sufficient iron supports myelination, neurotransmitter synthesis, and the development of memory, language, and learning abilities. Conversely, iron deficiency during the first 1000 days of life is associated with reduced cognitive function, developmental delays, and an increased risk of long-term neurocognitive disorders.Conclusion: Optimal iron intake during the first 1000 days of life is essential to support maximal brain development, prevent long-term cognitive impairments, and enhance children’s future intellectual potential.